The Determinants of Employee Performance and Employee Job Loyalty as an Intervening Variable at Electronic Factory in Bekasi Indonesia - Fauziah, Rachma; Panjaitan, Saur (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
With job loyalty acting as an intervening variable, this study attempts to examine how workload and work engagement affect employee performance at PT Emsonic Indonesia. One of the most important elements in a company's success is employee performance, but a number of issues, including excessive workloads and subpar employee loyalty, can have an impact on overall performance. Using LISREL 8.80, the study methodology employs SEM (Structural Equation Modeling) analysis to quantify both direct and indirect correlations between variables. This study used a questionnaire survey to gather data from PT Emsonic Indonesia employees who were chosen at random. The results showed that work engagement and workload significantly affected employee performance. Job loyalty did not significantly mediate the relationship between workload and performance, but it did mediate the association between work engagement and performance. These results indicate that in order to establish a work environment that fosters employee loyalty and enhances employee performance, PT Emsonic Indonesia must raise employee engagement and manage workload as efficiently as possible.